2016
DOI: 10.1039/c6ob00298f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of N-naphthoyl-phenylglyoxamide-based small molecular antimicrobial peptide mimics as novel antimicrobial agents and biofilm inhibitors

Abstract: Antimicrobial peptides (AMPs) are a key component of the human immune system. Synthetic AMP mimics represent a novel strategy to counteract the increasing incidence of antimicrobial resistance. Here, we describe the synthesis of novel glyoxamide derivatives via ring-opening reactions of N-hexanoyl, N-benzoyl and N-naphthoylisatins with N,N-dimethylethane-1,2-diamine and N,N-dimethylpropane-1,3-diamine. These were converted to both the hydrochloric acid (HCl) or quaternary ammonium iodide (MeI) salts and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…Membrane capacitance is directly influenced by membrane thickness and/or the water content at the bilayer. As a positive control, a pore-inducing cathelicidin peptide, LL-37, was later added (Turner et al, 1998;Nizalapur et al, 2016). This addition of LL-37 induced a definite change in membrane conduction and membrane capacitance.…”
Section: Resultsmentioning
confidence: 99%
“…Membrane capacitance is directly influenced by membrane thickness and/or the water content at the bilayer. As a positive control, a pore-inducing cathelicidin peptide, LL-37, was later added (Turner et al, 1998;Nizalapur et al, 2016). This addition of LL-37 induced a definite change in membrane conduction and membrane capacitance.…”
Section: Resultsmentioning
confidence: 99%
“…To test how selected potent phenylglyoxamide compounds ( 27 a, 26 b , 34 d , 35 d ) might interact with cell membranes, tethered bilayer lipid membrane (tBLM) technology was used in conjunction with electrical impedance spectroscopy ,. By anchoring a lipid membrane onto a gold substrate, it is possible to measure changes in intrinsic membrane conduction in real time upon addition of the compounds.…”
Section: Resultsmentioning
confidence: 99%
“…N ‐Aryl, N ‐acyl or N ‐sulfonylisatins 4 (Figure ) can undergo ring‐opening reaction with alcohols and amines to yield the corresponding phenylglyoxamides . Recently, our research group has reported that N ‐naphthoyl‐phenylglyoxamide derivative 5 (Figure ) possessed moderate to high antibacterial activities against the common bacterial pathogens Staphylococcus aureus and Pseudomonas aeruginosa . These phenylglyoxamides can be synthesised by the ring‐opening reaction of N ‐sulfonylisatin with amines.…”
Section: Introductionmentioning
confidence: 99%
“…Our research group has recently synthesized short glyoxamide-based peptidomimetics via the ring-opening reaction of Nnaphthoylisatins with amines and amino acids [34,35]. As part of an ongoing program to develop short antimicrobial peptidomimetics, we were interested in utilizing the biphenyl backbone due to its frequent presence in medicinal chemistry [36,37].…”
Section: Introductionmentioning
confidence: 99%